Agreement of Waqf in Indonesia and Malaysia: Harmonisation with Quranic Principles and Modern Legal Frameworks - Anggriani, Reni; Farhanin Abdullah Asuhaimi; Jarot Wahyudi; Fauziah, Nafiza; Fadhilah Abdullah Asuhaimi (Ijtihad : Jurnal Wacana Hukum Islam dan Kemanusiaan, 2025)
This research aims to find out the harmonisation of waqf agreements in Indonesia and Malaysia with Quranic principles and modern legal frameworks, with an emphasis on the role of agreements in waqf management. The agreement, in this context, refers to a legal action between the Waqif (waqf giver) and the Nadzir (waqf recipient/manager), who have rights and obligations regarding the provision of land as waqf, as recorded through the Waqf Pledge Law. This agreement provides legal certainty and guarantees the rights and obligations of the parties, as well as fulfilling the command of the Quran Surah Al Maidah verse 2 to ”help each other in kindness and piety“. The research applies normative and qualitative approaches. The primary legal source was obtained through interviews, and the secondary data included Indonesian Law No. 41 of 2004 concerning Waqf in Indonesia, and relevant state-level waqf laws in Malaysia. The study shows that a harmonisation of the rules governing waqf management agreements applies in both Indonesia and Malaysia, based on the Quran, Surah Al Maidah, verse 2. This article contributes to strengthening knowledge in the law of waqf agreements, especially the harmonisation of waqf management in Indonesia and Malaysia.